IL-6 Induced by Periodontal Inflammation Causes Neuroinflammation and Disrupts the Blood–Brain Barrier - Furutama, Daisuke (Brain Sci, 2020)
Background: Periodontal disease (PD) is a risk factor for systemic diseases, including neurodegenerative diseases. The role of the local and systemic inflammation induced by PD in neuroinflammation currently remains unclear. The present study investigated the involvement of periodontal inflammation in neuroinflammation and blood–brain barrier (BBB) disruption. Methods: To induce PD in mice (c57/BL6), a ligature was placed around the second maxillary molar. Periodontal, systemic, and neuroinflammation were assessed based on the inflammatory cytokine mRNA or protein levels using qPCR and ELISA. The BBB permeability was evaluated by the mRNA levels and protein levels of tight junction-related proteins in the hippocampus using qPCR and immunofluorescence. Dextran tracing in the hippocampus was also conducted to examine the role of periodontal inflammation in BBB disruption. Results: The TNF-α, IL-1β, and IL-6 levels markedly increased in gingival tissue 1 week after ligation. The IL-6 serum levels were also increased by ligature-induced PD. In the hippocampus, the IL-1β mRNA expression levels were significantly increased by ligature-induced PD through serum IL-6. The ligature-induced PD decreased the claudin 5 expression levels in the hippocampus, and the neutralization of IL-6 restored its levels. The extravascular 3-kDa dextran levels were increased by ligature-induced PD. Conclusions: These results suggest that the periodontal inflammation-induced expression of IL-6 is related to neuroinflammation and BBB disruption in the hippocampus, ultimately leading to cognitive impairment. Periodontal therapy may protect against neurodegenerative diseases.